Sistem Informasi Data Agenda Surat Di Kantor Kecamatan Kedunggalar Ngawi - Jati, Mohammad Syah Hayuning; Naafian, Nuur Rochman; Wibowo, Kresno Ario Tri (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
The Kedunggalar sub-district office is one of the agencies that administrates incoming and outgoing mail in its agency. The administration system is still done manually by recording on the agenda book which causes storage limitations, difficulties in the data search process and is vulnerable to data loss. Based on these problems, the formulation of the problem raised is how to create an incoming and outgoing mail information system. Information systems designed are able to manage data on the origin of letters, the destination of letters, incoming mail and outgoing mail. The method that the author uses is SDLC (System Development Life Cycle) using PHP programming language and MySQL database. The information system that the author designed is expected to be able to assist the mail administration department in managing incoming and outgoing mail data so that it can be used effectively and efficiently.Kantor Kecamatan Kedunggalar adalah salah satu instansi yang melakukan administrasi pada surat yang masuk dan keluar di instansinya. Sistem administrasi tersebut masih dilakukan secara manual dengan mencatat pada buku agenda yang menyebabkan keterbatasan penyimpanan, kesulitan dalam proses pencarian data dan rentan terhadap kehilangan data. Berdasarkan masalah tersebut rumusan masalah yang diangkat adalah bagaimana membuat sistem informasi surat masuk dan keluar. Sistem informasi yang dirancang mampu mengelola data asal surat, tujuan surat, surat masuk dan surat keluar. Metode yang penulis gunakan adalah SDLC (System Development Life Cycle) menggunakan Bahasa pemrograman PHP dan basis data MySQL. Sistem informasi yang penulis rancang diharapkan mampu membantu bagian administrasi surat dalam mengelola data surat yang masuk dan keluar agar dapat digunakan denganefektif dan efisien.